5. ASSESSMENT OF SLEEP QUALITY USING THE PSQI SCORE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE TREATED AS OUTPATIENTS AT BACH MAI HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objectives: Sleep disorders in patients with chronic obstructive pulmonary disease (COPD) are very common, but have received little clinical attention. These sleep disorders affect daily activities and the effectiveness of treatment.Methods: This study was conducted to evaluate sleep quality in patients with COPD.Methods: A cross-sectional descriptive study was conducted on a sample size of 109 COPD patients receiving outpatient treatment at the Examination Department - Bach Mai Hospital from March 2025 to April 2025. The research tool Pittsburg Sleep Quality Index (PSQI) is used. Patients completed a questionnaire to assess their sleep quality by PSQI tool.Results: 69,7% of COPD patients (n=109) reported poor sleep quality (PSQI>5).Conclusion: The rate of COPD patients with sleep disorders is very high. There are many adverse events affecting sleep quality that need to be considered by clinicians to develop effective intervention strategies.
Keywords: PSQI; sleep quality; chronic obstructive pulmonary disease